2014
DOI: 10.1108/jsbed-04-2014-0056
|View full text |Cite
|
Sign up to set email alerts
|

Strategic positioning and strategic types of small firms

Abstract: Purpose – The purpose of this paper is to study the strategic process of small- and medium-sized enterprises (SMEs) including strategic reference points (SRP) (Fiegenbaum et al., 1996). Design/methodology/approach – The paper identifies the strategic positioning of SMEs (Lavie and Fiegenbaum, 2000, 2003) according to the importance that their managers give to internal and external SRP. Their influence on strategic types (Miles and Snow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…This allows for an in-depth empirical study of differences found between dairy farmers in their perception of opportunities. Studies of strategic decision-making in small businesses have revealed that the business owners' perception of opportunities is more decisive in the selection of a strategy than the formal analyses of opportunities [13,14]. For this reason, a better understanding of differences in the perception of opportunities is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for an in-depth empirical study of differences found between dairy farmers in their perception of opportunities. Studies of strategic decision-making in small businesses have revealed that the business owners' perception of opportunities is more decisive in the selection of a strategy than the formal analyses of opportunities [13,14]. For this reason, a better understanding of differences in the perception of opportunities is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The perception is found to be more important than a formal analysis (Parnell et al 2000;García-Pérez et al 2014). The perception of opportunities is influenced by dominant paradigms, lock-in effects and path dependencies (Vanloqueren and Baret 2009;Lamine et al 2012;Cowan and Gunby 1996).…”
Section: Strategic Decision-makingmentioning
confidence: 94%
“…This allows for an in-depth empirical study of differences between dairy farmers in their perception of opportunities. In the study of strategic decisionmaking in small business, the perception of opportunities is found to be more decisive for the outcome than the formal analyses (Parnell et al 2000;García-Pérez et al 2014).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations